2015
DOI: 10.21608/jppp.2015.53254
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Resistance Against Rhizoctonia Root Rot of Common Bean

Abstract: The effect of seed treatments of common bean plants (cv. Nebraska) with Bion, Salicylic Acid (SA) and Paenibacillus polymyxa on infection with Rhizoctonia solani under greenhouse and field conditions was investigated. In greenhouse experiment, all treatments decreased percentages of pre and post-emergence damping-off compared with control grown in infested soil by R. solani. The highest percentage of survival plants was achieved from treatment with Bion 5mM (80%) followed by each of Bion 3mM and SA 5mM (76.7%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 64 publications
(77 reference statements)
0
2
0
1
Order By: Relevance
“…These results are in agreement with those obtained by several authors. Shehata (2015) found that treatment common bean seeds with Rhizolex-T reduced percentage of pre-and post-emergence damping-off, increased the percentage of healthy survival plants and significantly increased number of pods/plant and seed yield compared with untreated control. Under field conditions highest reduction in the diseases incidences and increases in the percentages of bean yield (number and weight of pods plant -1 and dry weight of 100 seeds) were induced by T. harzianum, followed by T. viride when used as seed treatment (El-Fiki et al, 2014)…”
Section: Effect Of Seed Treatments On Some Agronomic Traits Of Common...mentioning
confidence: 91%
See 1 more Smart Citation
“…These results are in agreement with those obtained by several authors. Shehata (2015) found that treatment common bean seeds with Rhizolex-T reduced percentage of pre-and post-emergence damping-off, increased the percentage of healthy survival plants and significantly increased number of pods/plant and seed yield compared with untreated control. Under field conditions highest reduction in the diseases incidences and increases in the percentages of bean yield (number and weight of pods plant -1 and dry weight of 100 seeds) were induced by T. harzianum, followed by T. viride when used as seed treatment (El-Fiki et al, 2014)…”
Section: Effect Of Seed Treatments On Some Agronomic Traits Of Common...mentioning
confidence: 91%
“…The total cultivated area of common bean in Egypt in 2018 reached 120729 feddans that yielded 122870 tons (Anonymous, 2018). Also, bean is known by many other names such as common bean (Abeysinghe, 2007;Mahamune and Kakde, 2011;Shehata, 2015 andHussein et al, 2018), bean (Kataria et al, 2002;Sallam, Nashwa et al, 2008;El-Fiki et al, 2014 andRagab, Mona et al, 2015), dry bean (Abd-El-Khair et al, 2019 andJacobs et al, 2019), French bean, Rajma (Hindi), haricot bean, snap bean, navy bean (Mahamune and Kakde, 2011;Yunsheng et al, 2015 and, kidney bean (Mahamune andKakde, 2011 andAbd El-Hai andAli, Abeer, 2018) and finally bean which commonly known in Egypt as Phasolia is a member of family Fabaceae (Nassar, Rania et al, 2011 andYunsheng et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…79-198279- -N, 79-198479- -N e 79-198779- -N (ZAPATA et al, 1985. -1981- -14, 79-1982- -N, 79-1984- -N, 79-1987- -N (ZAPATA et al, 1985, IAPAR 14 e IAPAR 16 (MARINGONI et al , 1992a) Têm-se constatada resistência foliar à X. campestrls pv. phaseoll (OLEAS-ARIAS, 1982;RAVA, 1985).…”
Section: Phaseoliunclassified